Implementation of Core Competency and Life Cycle Assesment (LCA) In the CID Program Petani Maju 4.0 of PT Pertamina Hulu Mahakam - Lalu Muhammad Azwar; Ahmad Yuli; Kris Radityorini; Nustatul Jannah; Riana Rahmaningrum (Prospect Publishing, 2023)
This article aims to describe the importance of integrating the concept of Life Cycle Assessment (LCA) in the Community Involvement Development (CID) program. Based on Permen LHK 1/2021 concerning Proper, LCA must be the basis for every company to develop programs based on community empowerment. This article provides an overview of the case studies in PT Pertamina Hulu Mahakam's CSR 4.0 Maju Farmer program which has integrated linkages with LCA. The LCA study of PT Pertamina Hulu Mahakam covers the cradle-to-grave function unit. Cradle-to-grave function The product systems studied for life cycle assessment have covered 100% of products, namely petroleum, natural gas and condensate production systems. The oil and gas production process certainly has an impact on the activities of people's lives which must be explained with a CSR-based community empowerment approach. The results of the integration of LCA and the CSR program of Farmers Maju 4.0 were able to utilize the company's 33 tons of organic waste into compost and alternative feed for livestock. As well as environmental improvements, it can contribute to reducing greenhouse gas emissions by 259.2 kilograms of methane gas per year.